This is not banal or the image as poetic of the banal - BOUZIDA, Fethi; ELLOUMI, Ali (Advances in Social Sciences Research Journal, 2021)
Our objective in this article is to ask the question of the conceptual contribution of René Magritte’s work through its relationship with meaning. Beyond trying to express the meaning of his images. Rather, it is to infringe the notion of the "banal" that Magritte has certainly articulated in his work. What is at stake in Magritte’s work escapes meaning. So we are faced with an image in itself, in its poetic dimension ; thought-out production of visibility which calls for a view uncluttered from all eyes. In short, an image that sends us back to a pure visual perception.